2011
DOI: 10.1007/s12562-011-0345-8
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal activity and identification of an algicidal substance produced by marine Pseudomonas sp. C55a-2

Abstract: A substance produced extracellularly by a marine bacterium, Pseudomonas C55a-2 strain, and possessing algal-killing activity against a diatom, Chaetoceros ceratosporum, was isolated from the culture supernatant of the bacterium in order to identify its chemical structure. The algicidal substance extracted with ethyl acetate from the culture supernatant was purified by using Sep-Pak treatment, reverse phase column chromatography with Sephadex LH-20, and high performance liquid chromatography (HPLC) with Mightys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 19 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…Strain A2 was identified by phenotypic characterization and 16S rRNA sequence analysis to the genus Acinetobacter and identified by partial sequence analysis of the rpoB gene to A. guillouiae, a species found in human clinical and in environmental specimens [26]. Alteromonas and Pseudoalteromonas of the gproteobacteria have been found to be the most dominant genera among the known algicidal bacteria [20,23,33]. Cytophaga, Flavobacterium and Bacillus were also frequently reported to possess algicidal activity [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Strain A2 was identified by phenotypic characterization and 16S rRNA sequence analysis to the genus Acinetobacter and identified by partial sequence analysis of the rpoB gene to A. guillouiae, a species found in human clinical and in environmental specimens [26]. Alteromonas and Pseudoalteromonas of the gproteobacteria have been found to be the most dominant genera among the known algicidal bacteria [20,23,33]. Cytophaga, Flavobacterium and Bacillus were also frequently reported to possess algicidal activity [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…L74 directly attacks A. flos-aquae by cell-to-cell contact. Cytophaga , Myxobacter , and Saprospira from aquatic systems exhibit algicidal abilities by direct attack; by contrast, Bacillus , Pseudomonas, Alteromonas , and Pseudoalteromonas exhibit algicidal activities by indirect attack [14]. Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…are common algicidal microorganisms [3,6,7]. These bacteria secrete algicidal substances, including proteins, peptides, amino acids, antibiotics, nitrogenous compounds, and alkaloids [814]. However, few algicidal compounds have been isolated and purified.…”
Section: Introductionmentioning
confidence: 99%
“…At least some algicidal bacteria might kill prey algae by using some kinds of proteases. As other algicidal substances, Isatin and red pigments of prodigiosins were identifi ed from marine algicidal bacteria (Nakashima et al 2006 ;Kim et al 2008b ;Sakata et al 2011 ). Skerratt et al ( 2002 ) showed that Gram-negative algicidal bacteria appear to use the AI-2 mechanism (quorum sensing) at the mid-to late stage of the log growth phase.…”
Section: Characteristics Of Algicidal Bacteriamentioning
confidence: 99%